The biological impacts of the Fukushima nuclear accident on the pale grass blue butterfly - Hiyama, Atsuki (Nature Publishing Group, 2012)
The collapse of the Fukushima Dai-ichi Nuclear Power Plant caused a massive release of radioactive materials to the environment. A prompt and reliable system for evaluating the biological impacts of this accident on animals has not been available. Here we show that the accident caused physiological and genetic damage to the pale grass blue Zizeeria maha, a common lycaenid butterfly in Japan. We collected the first-voltine adults in the Fukushima area in May 2011, some of which showed relatively mild abnormalities. The F(1) offspring from the first-voltine females showed more severe abnormalities, which were inherited by the F(2) generation. Adult butterflies collected in September 2011 showed more severe abnormalities than those collected in May. Similar abnormalities were experimentally reproduced in individuals from a non-contaminated area by external and internal low-dose exposures. We conclude that artificial radionuclides from the Fukushima Nuclear Power Plant caused physiological and genetic damage to this species.